“Llop Mougn” Film Animasi 2D Dengan Teknik Rotoscope - Oktivani Anggia Rahmalita; Mahendradewa Suminto (Journal of Animation and Games Studies, 2018)
Bedwetting habits are things that must have been experienced by everyone, especially young children, and various methods were taken to stop this. The lack of knowledge of some people in the past will be something that believes in myth. The myth of biting the navel by dragonflies is believed to stop the bedwetting habit. This is what then based on personal experience raises the idea of creating animated films because they are interesting and unique. added by using a combination storyline. Unify real events with dreams.The animated short film "Llop Mougn" tells a girl who believes that the myth of a belly button bitten by a dragonfly can stop the bedwetting habit, but when she does, she still wet the bed. The story is presented in the form of an animated 2D short film with an experimental genre, because this animated film has a plot that tends to jump and random plots so that it is not too easy to understand because in this film it does not tell the intent directly.The creation of this work uses the rotoscope process to explore techniques and get the results of a more realistic movement to get a different impression on the film. Keywords: bedwetting, experimental, rotoscope